2013
DOI: 10.1080/19393210.2012.721095
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and essential elements in conventional and home-produced eggs by ICP-MS analysis

Abstract: Concentrations of As, Ba, Cd, Co, Mn, Pb, Se, Sr, V, Cu, Fe, Mg, Zn and Mo were determined in conventional and home-produced eggs as sold in Brazil. Thirty-four conventional and 21 home-produced samples were obtained in different Brazilian cities. Elements were determined by inductively coupled plasma mass spectrometry (ICP-MS). Concentrations of Ba, Cd, Co, Pb, Se, Fe, Zn and Mo in conventional and home-produced eggs differed (statistically significant). Correlations were found among the other elements in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Taking into account the differences in the production system between free‐range and battery eggs, a differentiated pattern in mineral concentration has previously been demonstrated (Overmeire and others ; Giannenas and others ; Batista and others ; Freitas and others ). Thus, if a chemical element composition database is defined, data mining tools, such as decision trees and naïve Bayes (NB) algorithms, can be used to identify the group to which a new sample belongs after a preliminary group classification (Mutihac and Mutihac ).…”
Section: Introductionmentioning
confidence: 86%
“…Taking into account the differences in the production system between free‐range and battery eggs, a differentiated pattern in mineral concentration has previously been demonstrated (Overmeire and others ; Giannenas and others ; Batista and others ; Freitas and others ). Thus, if a chemical element composition database is defined, data mining tools, such as decision trees and naïve Bayes (NB) algorithms, can be used to identify the group to which a new sample belongs after a preliminary group classification (Mutihac and Mutihac ).…”
Section: Introductionmentioning
confidence: 86%
“…Contrary to a previous report from Vincevica-Gaile et al, 30 who found a wide range of concentrations in hen eggs grown in Latvian organic farms, Brazilian organic and regular eggs presented elemental compositions within narrow concentration ranges. In a previous study from our research group, de Freitas et al 31 determined trace element concentrations in commercial and free-range whole chicken eggs sold in different Brazilian regions. A wider range of concentrations for ordinary and free-range eggs than in the present study was found.…”
Section: Elemental Concentrations In Egg Samplesmentioning
confidence: 99%
“…de Freitas et al 31 reported As levels in Brazilian egg samples ranging from 23 AE 2 to 21.5 AE 8.5 ng g À1 (AE is the standard deviation, SD) for ordinary and free-range egg samples, respectively. According to the Codex Alimentarius Commission 32 the acceptable limit for this toxic element in eggs and their derivatives is 500 ng g À1 .…”
Section: Elemental Concentrations In Egg Samplesmentioning
confidence: 99%
“…Compared with the above methods, ICP‐MS has the superiority of wide linear range, high sensitivity, high throughput, and strong antimatrix interference ability (Jiang, Huang, et al., 2020 ; Yin et al., 2020 ). It has been used in the applications of multicomponent metal elements in red wine, grain, meat, and eggs (de Freitas et al., 2013 ; Persson et al., 2009 ; Song et al., 2020 ; Vacchina et al., 2020 ). Therefore, ICP‐MS provides an ideal tool for the simultaneous detection of multicomponent heavy metals in food.…”
Section: Introductionmentioning
confidence: 99%